2022
DOI: 10.1096/fj.202200757r
|View full text |Cite
|
Sign up to set email alerts
|

Insulin stimulates atypical protein kinase C‐mediated phosphorylation of the neuronal adaptor FE65 to potentiate neurite outgrowth by activating ARF6‐Rac1 signaling

Abstract: Neurite outgrowth is a fundamental process in neurons that produces extensions and, consequently, neural connectivity. Neurite damage and atrophy are observed in various brain injuries and disorders. Understanding the intrinsic pathways of neurite outgrowth is essential for developing strategies to stimulate neurite regeneration.Insulin is a pivotal hormone in the regulation of glucose homeostasis. There is increasing evidence for the neurotrophic functions of insulin, including the induction of neurite outgro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…S1a–c ). Intriguingly, Fe65 has also been implicated in different functions such as insulin based potentiation of neurite outgrowth, 43 , 44 which could be further analyzed in the context of AD therapeutics. It is worth noting that Fe65-EXO could efficiently bind or be internalized by neuronal cells with APP overexpressed at a high magnitude, suggesting a capacity of Fe65-EXO to target APP overexpressed neuronal cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…S1a–c ). Intriguingly, Fe65 has also been implicated in different functions such as insulin based potentiation of neurite outgrowth, 43 , 44 which could be further analyzed in the context of AD therapeutics. It is worth noting that Fe65-EXO could efficiently bind or be internalized by neuronal cells with APP overexpressed at a high magnitude, suggesting a capacity of Fe65-EXO to target APP overexpressed neuronal cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanism has not been fully explored, it is generally achieved by insulin-activating Ras-related C3 botulinum toxin substrate 1 (Rac1). Rac1 is a small GTP enzyme associated with axonal growth ( 49 ). It can be observed that the PKC pathway involves multiple molecular pathways, and how to selectively utilize the PKC pathway is the problem we are facing.…”
Section: Mechanismmentioning
confidence: 99%